2009
DOI: 10.1111/j.1365-2435.2008.01537.x
|View full text |Cite
|
Sign up to set email alerts
|

Animal temperature limits and ecological relevance: effects of size, activity and rates of change

Abstract: Summary 1.Climate change is affecting species distributions and will increasingly do so. However, current understanding of which individuals and species are most likely to survive and why is poor. Knowledge of assemblage or community level effects is limited and the balance of mechanisms that are important over different time-scales is poorly described. Laboratory experiments on marine animals predominantly employ rates of change 10-100 000 times faster than climate induced oceanic warming. To address this fai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
186
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 320 publications
(207 citation statements)
references
References 64 publications
11
186
0
1
Order By: Relevance
“…Results of the studies on the other Southern Ocean invertebrates demonstrated their low tolerance to warming especially when concerning low activity taxa (Peck et al 2009). This fact is quite important in the context of the latest discussion about the possibility of describing new taxa before they go extinct, especially in case of poorly studied groups such as, e.g., tanaidaceans (Mora et al 2011;Costello et al 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Results of the studies on the other Southern Ocean invertebrates demonstrated their low tolerance to warming especially when concerning low activity taxa (Peck et al 2009). This fact is quite important in the context of the latest discussion about the possibility of describing new taxa before they go extinct, especially in case of poorly studied groups such as, e.g., tanaidaceans (Mora et al 2011;Costello et al 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Prediction of the ecological ramifications of facets of climate change is particularly difficult due to inherent confounds of interactions between dissolved oxygen concentration and temperature (Peck et al 2009 (Broitman et al 2009). However, here we have shown that by using comparative functional response analyses, in a similar way to invasive species impact predictions Wasserman et al 2016b), it is possible to identify the impact of a predator under various warming scenarios and assess whether there are interaction effects when both sides of the predator-prey dynamic are considered.…”
Section: Discussionmentioning
confidence: 99%
“…Animals were kept in 40 L aquariums of similar salinity (27 PSU) as the collection site. Aquarium water temperatures were lowered to holding temperature (1 °C) at a rate of 1 °C day −1 , using 0.5 °C steps in the morning and afternoon (Peck et al 2009a). Mussels were allowed to acclimate to laboratory conditions for 4 weeks prior to respiration measurements, and water temperature was maintained at 1 ± 0.20 °C throughout the experimental period.…”
Section: Collection Sites Animals and Holding Conditionsmentioning
confidence: 99%